An anthology of the Cambridge Platonists
1 online resource
Keywords: Notwithstanding their neglect in many histories of ideas in the West, the Cambridge Platonists constitute the most significant and influential group of thinkers in the Platonic tradition between the Florentine Renaissance and the Romantic Age. This anthology offers readers a unique, thematically structured compendium of their key texts, along with an extensive introduction and a detailed account of their legacy. The volume draws upon a resurgence of interest in thinkers such as Benjamin Whichcote, 1609-1683; Ralph Cudworth, 1618-1688; Henry More, 1614-1687; John Smith, 1618-1652, and Anne Conway 1631-1679, and includes hitherto neglected extracts and some works of less familiar authors within the group, like George Rust 1627?-1670; Joseph Glanvill, 1636-1680, and John Norris 1657-1712. It also highlights the Cambridge Platonists' important role in the history of philosophy and theology, influencing luminaries such as Shaftesbury, Berkeley, Leibniz, Joseph de Maistre, S.T. Coleridge, and W.R. Emerson. An Anthology of the Cambridge Platonists is an indispensable guide to the serious study of a pivotal group of Western metaphysicians and is of great value for both students and scholars of philosophy, literature, history, and theology. Key Features The only systematic anthology to the Cambridge Platonists available, facilitating quick comprehension of key themes and ideas Uses new translations of the Latin works, vastly improving upon faulty and misleading earlier translations Offers a wide range of new perspective on the Cambridge Platonists, showing the extent of their influence in early modern philosophy and beyond.